Inhibition of Leishmania infantum Trypanothione Reductase by New Aminopropanone Derivatives Interacting with the NADPH Binding Site - Valentina Noemi Madia; Davide Ialongo; Elisa Patacchini; Cécile Exertier; Lorenzo Antonelli; Gianni Colotti; Antonella Messore; Valeria Tudino; Francesco Saccoliti; Luigi Scipione; Andrea Ilari; Roberta Costi; et al. (Molecules, 2023)
Background: As a result of the paucity of treatment, Leishmaniasis continues to provoke about 60,000 deaths every year worldwide. New molecules are needed, and drug discovery research is oriented toward targeting proteins crucial for parasite survival. Among them, trypanothione reductase (TR) is of remarkable interest owing to its vital role in Leishmania species protozoan parasite life. Our previously identified compound 1 is a novel chemotype endowed with a unique mode of TR inhibition thanks to its binding to a formerly unknown but druggable site at the entrance of the NADPH binding cavity, absent in human glutathione reductase (hGR). Methods: We designed and synthesized new 3-amino-1-arylpropan-1-one derivatives structurally related to compound 1 and evaluated their potential inhibition activity on TR from Leishmania infantum (LiTR). Cluster docking was performed to assess the binding poses of the compounds. Results: The newly synthesized compounds were screened at a concentration of 100 μM in in vitro assays and all of them proved to be active with residual activity percentages lower than 75%. Conclusions: Compounds 2a and 2b were the most potent inhibitors found, suggesting that an additional aromatic ring might be promising for enzymatic inhibition. Further structure–activity relationships are needed to optimize our compounds activity.